The End of Neoliberalism? - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2003)
This article was commissioned by the French newspaper Le Monde. The newspaper was one of several sponsors of an International Conference on Global Regulation, held at the University of Sussex on May 29-31, 2003, where we presented a plenary paper. As part of its sponsorship, Le Monde agreed to publish two articles reflecting the spirit of the conference. The first of these articles, written by four of the conference organizers, was published prior to the conference. After the conference, the organizers asked the two of us to submit a second, short article highlighting the gist of our presentation. This article is enclosed below. The paper was sent by the organizers to Le Monde's Editor in Chief, Serge Marti. Many phone calls followed. In each call, Mr. Marti promised to publish the paper promptly. He never did.
Keywords: 330; accumulation; capital; capitalism; conflict; crisis; deflation; distribution; elite; energy; finance; globalization; growth; imperialism; inflation; liberalism; Middle East; military; national interest; Iraq; neoliberalism; oil; OPEC; ownership; peace; po